Influence of Brownian Motion, Thermophoresis and Magnetic Effects on a Fluid Containing Nanoparticles Flowing over a Stretchable Cylinder - Majeed, Aaqib; Zeeshan, Ahmad (Fluid dynamics & materials processing, 2024)
The influence of Brownian motion and thermophoresis on a fluid containing nanoparticles flowing over a stretchable cylinder is examined. The classical Navier-Stokes equations are considered in a porous frame. In addition, the Lorentz force is taken into account. The controlling coupled nonlinear partial differential equations are transformed into a system of first order ordinary differential equations by means of a similarity transformation. The resulting system of equations is solved by employing a shooting approach properly implemented in MATLAB. The evolution of the boundary layer and the growing velocity is shown graphically together with the related profiles of concentration and temperature. The magnetic field has a different influence (in terms of trends) on velocity and concentration.